Discovery of a Novel Stem Rust Resistance Allele in Durum Wheat that Exhibits Differential Reactions to Ug99 Isolates. Issue 10 (1st October 2017) - Nirmala, Jayaveeramuthu; Saini, Jyoti; Newcomb, Maria; Olivera, Pablo; Gale, Sam; Klindworth, Daryl; Elias, Elias; Talbert, Luther; Chao, Shiaoman; Faris, Justin; Xu, Steven; Jin, Yue; et al.
Abstract: Wheat stem rust, caused by Puccinia graminis f. sp. tritici Eriks. & E. Henn, can incur yield losses in susceptible cultivars of durum wheat, Triticum turgidum ssp. durum (Desf.) Husnot. Although several durum cultivars possess the stem rust resistance gene Sr13, additional genes in durum wheat effective against emerging virulent races have not been described. Durum line 8155-B1 confers resistance against the P. graminis f. sp. tritici race TTKST, the variant race of the Ug99 race group with additional virulence to wheat stem rust resistance gene Sr24 . However, 8155-B1 does not confer resistance to the first-described race in the Ug99 race group: TTKSK. We mapped a single gene conferring resistance in 8155-B1 against race TTKST, Sr8155B1, to chromosome arm 6AS by utilizing Rusty/8155-B1 and Rusty*2/8155-B1 populations and the 90K Infinium iSelect Custom bead chip supplemented by KASP assays. One marker, KASP_6AS_IWB10558, cosegregated with Sr8155B1 in both populations and correctly predicted Sr8155B1 presence or absence in 11 durum cultivars tested. We confirmed the presence of Sr8155B1 in cultivar Mountrail by mapping in the population Choteau/Mountrail. The marker developed in this study could be used to predict the presence of resistance to race TTKST in uncharacterized durum breeding lines, and also to combine Sr8155B1 with resistance genes effective to Ug99 such as Sr13 . The map location of Sr8155B1 cannot rule out the possibility that this gene is an allele at the Sr8 locus. However, race specificity indicates that Sr8155B1 is different from the known alleles Sr8a and Sr8b .